Strontium Modified Calcium Sulfate Hemihydrate Scaffold Incorporating Ginsenoside Rg1/Gelatin Microspheres for Bone Regeneration - Luo, Peng; Yu, Lan; Lin, Qiang; Wang, Changde; Yang, Dazhi; Tang, Shuo (Frontiers in Bioengineering and Biotechnology, 2020)
The aim of this study was to prepare a promising biomaterial for bone tissue repair and regeneration. The Strontium- calcium sulfate hemihydrate (Sr-α-CaS) scaffold loading gelatin microspheres (GMs) with Ginsenoside Rg1 (Rg1) was designed. The scaffolds of Rg1/GMs/Sr-α-CaS showed sustained release of Rg1, good biocompatibility and ability of promoting osteogenic differentiation and angiogenesis in vitro. The scaffolds were implanted into animal model of cranial bone defect to characterize bone tissue repair and regeneration in vivo. From the images of Micro-CT, it was obvious that the most bone tissue was formed in Rg1/GMs/Sr-α-CaS group in 12 w. New bone structure, collagen and mineralization were analyzed with staining of HE, Masson and Safranin O- Fast green and showed good distribution. The expression of osteocalcin of Rg1/GMs/Sr-α-CaS showed new bone formation in defect site. The results revealed that synergy of Rg1 and Sr showed the best effect of bone repair and regeneration, which provided a new candidate for bone defect in clinic.